Elemental Quantitative Distribution and Statistical Analysis on Cross Section of Stainless Steel Sheet by Laser Ablation Inductively Coupled Plasma Mass Spectrometry - LUO, Qian-hua; WANG, Hai-zhou (Journal of iron and steel research, international, 2015)
An innovative application of laser ablation inductively coupled plasma mass spectrometry （LA-ICP-MS） technique in illustrating elemental distributions on stainless steel sheets was presented. The technique proved to be a systematic and accurate ap- proach in producing visual images or maps of elemental distributions at cross-sectional surface of a stainless steel sheet. Two stain- less steel sheets served as research objects： 3 mm×l 300 mm hot-rolled stainless steel plate and 1 mm×l 260 mm cold-rolled plate. The cross-sectional surfaces of the two samples at 1/4 position along the width direction were scanned （raster area -44 mm2 and 11 mm2） with a focused laser beam （wavelength 213 nm, diameter of laser crater 100 μm, and laser power 1.6 mJ） in a laser abla- tion chamber. The laser ablation system was coupled to a quadrupole ICP-MS, which made the detection of ion intensities of 27A1＋, 44Ca＋, 47Ti-, 55Mn＋ and 56Fe＋ within an area of interest possible. One-dimensional （ID） content line distribution maps and two- dimensional （2D） contour maps for specific positions or areas were plotted to indicate the element distribution of a target area with high accuracy. Statistic method was used to analyze the acquired data by calculating median contents, maximum segregation, sta- tistic segregation and content-frequency distribution.